Measurement of quartz crystal resonators and filters in the production process - McCARTNEY, W. J. (Archives of Acoustics, 1991)
The crystal manufacturing industry has been plagued by measurement problems through out its history. Producers and customers have had problems monitoring product specifications with sufficient accuracy to unsure the final product meets the customer requirement. This problem is getting more severe where manufacturers are being pushed to provide very small lot production runs with high precision and low cost. This paper outlines some practical issues present for crystal producers and users. Several directions are presented to help minimize the problem. Key among these suggestions are the use of measurement techniques, fixtures and equipment compatible with current industry standards.